Revolutionizing nephrology research: expanding horizons with kidney-on-a-chip and beyond - Huang, Wei; Chen, Yi-Yuan; He, Fang-Fang; Zhang, Chun (Frontiers in Bioengineering and Biotechnology, 2024)
Organs-on-a-chip (OoC) is a microengineered three-dimensional cell culture system developed for decades. Utilizing microfluidic technology, OoC cultivates cells on perfusable channels to construct in vitro organ models, enabling the simulation of organ-level functions under physiological and pathophysiological conditions. The superior simulation capabilities compared to traditional animal experiments and two-dimensional cell cultures, making OoC a valuable tool for in vitro research.Recently, the application of OoC has extended to the field of nephrology, where it replicates various functional units, including glomerulus-on-a-chip, proximal tubule-on-a-chip, distal tubule-on-a-chip, collecting duct-on-a-chip, and even the entire nephron-on-a-chip to precisely emulate the structure and function of nephrons. Moreover, researchers have integrated kidney models into multi-organ systems, establishing human body-on-a-chip platforms. In this review, the diverse functional kidney units-on-a-chip and their versatile applications are outlined, such as drug nephrotoxicity screening, renal development studies, and investigations into the pathophysiological mechanisms of kidney diseases. The inherent advantages and current limitations of these OoC models are also examined.Finally, the synergy of kidney-on-a-chip with other emerging biomedical technologies are explored, such as bioengineered kidney and bioprinting, and a new insight for chip-based renal replacement therapy in the future are prospected.